The potential of native and engineered Clostridia for biomass biorefining - Ponsetto, Paola; Sasal, Emilia Malgorzata; Mazzoli, Roberto; Valetti, Francesca; Gilardi, Gianfranco (Frontiers in Bioengineering and Biotechnology, 2024)
Since their first industrial application in the acetone-butanol-ethanol (ABE) fermentation in the early 1900s, Clostridia have found large application in biomass biorefining. Overall, their fermentation products include organic acids (e.g., acetate, butyrate, lactate), short chain alcohols (e.g., ethanol, n-butanol, isobutanol), diols (e.g., 1,2-propanediol, 1,3-propanediol) and H2 which have several applications such as fuels, building block chemicals, solvents, food and cosmetic additives. Advantageously, several clostridial strains are able to use cheap feedstocks such as lignocellulosic biomass, food waste, glycerol or C1-gases (CO2, CO) which confer them additional potential as key players for the development of processes less dependent from fossil fuels and with reduced greenhouse gas emissions. The present review aims to provide a survey of research progress aimed at developing Clostridium-mediated biomass fermentation processes, especially as regards strain improvement by metabolic engineering.